2021
DOI: 10.4103/picr.picr_58_19
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of patient information leaflet for coronary heart disease patients

Abstract: Background: Patient information leaflets (PILs) are effectively used to improve the patient's knowledge about medications, disease, diet, and lifestyle modifications. Aim: This study aims to develop and evaluate PILs for coronary heart disease patients. Materials and Methods: Primary, secondary, and tertiary resources were used to develop PILs. The developed PILs were validated by four doctors, four academic pharmacists, and one dietician. PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A similar mean age, male-female ratio, and educational background to Vinay et al were observed among HFrEF patients in this study in which the majority of patients (72.27%) were males with a mean age of 58.06± 8.35 and had either completed high school or primary school education. 30 Based on the ICC, the most commonly used statistical method to assess test-retest reliability, the developed UTQ is reliable in all three languages. Based on the results of an assimilation study conducted to evaluate a PIL for haemodialysis patients, good reliability scores of 0.93 and 0.98 were obtained for Kannada and English UTQ, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar mean age, male-female ratio, and educational background to Vinay et al were observed among HFrEF patients in this study in which the majority of patients (72.27%) were males with a mean age of 58.06± 8.35 and had either completed high school or primary school education. 30 Based on the ICC, the most commonly used statistical method to assess test-retest reliability, the developed UTQ is reliable in all three languages. Based on the results of an assimilation study conducted to evaluate a PIL for haemodialysis patients, good reliability scores of 0.93 and 0.98 were obtained for Kannada and English UTQ, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A score ranging from 60 to 70 is generally acceptable. The readability of a document can be assessed using the following scale: very easy (90-100), easy (80-89), fairly easy (70-79), standard (60-69), fairly difficult (50-59), difficult (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and very confusing (0-29). 17 The PIL has been modified to improve its FRE/FKGL scores.…”
Section: Assessment Of Readability Of Leafletmentioning
confidence: 99%
“…[ 10 ] The method was previously used by studies concerned with assessing the ease of reading in India. [ 11 12 ]…”
Section: Methodsmentioning
confidence: 99%
“…18 The level of reading difficulty of the informed consent paper can be assessed using several measurements, including the Flesch Kincaid Grade Level which is a widely used readability formula and results in a reading grade equivalent to US grade level of education. 19,20 The Gunning Fog Index is also widely used and estimates the number of years of formal education that a reader needs to be able to understand the text, which can be helpful for assessing informed consent forms in other countries. There are many online tools available for calculating both scores, and the aim for informed consent and patient education materials should be for a reading level of US grade 6.…”
Section: Health Literacymentioning
confidence: 99%